A three-layer coated hollow silicon-based nanocomposite induced by bacteria and a preparation method and application thereof

CN122889734APending Publication Date: 2026-10-09LANXI ZHIDE ADVANCED MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611354343.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-02
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0010]本发明的目的之一在于提供一种细菌诱导成型的三层包覆空心硅基纳米复合材料,以解决现有技术中硅碳复合材料存在的层间界面结合力弱、结构稳定性差、空心结构制备工艺复杂、细菌利用方式单一、高温高能耗以及固废资源化利用率低的技术问题

Benefits of technology

第一,层次功能分工明确:纳米硅颗粒集中在内核,提供最大化的储锂活性位点;细菌碳作为中间层,利用其天生的粘附和包裹特性紧密贴合硅核,发挥最佳的界面缓冲效果;外层有机碳作为坚固外壳,保证整体导电性和结构完整性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122889734A_ABST
    Figure CN122889734A_ABST
Patent Text Reader

Abstract

The application provides a three-layer coated hollow silicon-based nanocomposite induced by bacteria, and a preparation method and application thereof, and relates to the technical field of nanocomposites, which comprises, from inside to outside, a nanosilicon particle core, a bacterial carbon isolation intermediate layer and an organic carbon coated outer layer. The nanosilicon particles are concentrated in the core to provide maximum lithium storage active sites. The bacterial carbon serves as the intermediate layer and closely adheres to the silicon core by virtue of its inherent adhesion and wrapping properties to achieve optimal interface buffering effect. The outer layer of organic carbon serves as a strong shell to ensure overall electrical conductivity and structural integrity. During charging and discharging, the expansion force of the inner core silicon is transmitted from inside to outside, first passes through the flexible bacterial carbon intermediate layer for buffering and reduction, and then is transmitted to the outer layer of hard carbon, so that the overall cracking can be more effectively inhibited. The functional groups retained in the bacterial carbon intermediate layer form strong hydrogen bonds or chemical bonds with the hydroxyl groups and other groups on the surface of the nanosilicon in the core, and are compatible with the oxygen-containing groups of the outer layer of organic carbon, so that the interface bonding strength is high.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of nanocomposite materials technology, and in particular to a bacterial-induced three-layer coated hollow silicon-based nanocomposite material, its preparation method, and its application. Background Technology

[0002] Silicon-based materials are considered important candidates for next-generation lithium-ion battery anode materials due to their extremely high theoretical specific capacity (approximately 4200 mAh / g). However, silicon-based anode materials face two major bottlenecks in practical applications: first, silicon undergoes enormous volume expansion (up to 300% or more) during charge and discharge, leading to electrode material pulverization and structural collapse, severely affecting cycle stability; second, silicon's intrinsic electronic conductivity is low, limiting its rate performance. To address these issues, researchers have developed various silicon-carbon composite strategies, employing techniques such as carbon coating, nanostructuring, and porous structure design to mitigate volume effects and improve conductivity.

[0003] In the field of silicon-carbon composites, existing research has utilized bacterial cellulose as a carbon source precursor to obtain three-dimensional conductive networked silicon-carbon composites through high-temperature carbonization. For example, Li Xianglong et al. prepared three-dimensional conductive networked silicon-carbon composites by shearing and mixing silicon nanomaterials, bacterial cellulose, and dispersants, followed by high-temperature annealing. Er Jianwei et al. prepared carbon-coated nano-silicon-carbon composites by freeze-drying bacterial cellulose hydrogels followed by high-temperature carbonization, and then depositing a nano-silicon layer and a carbon coating layer using a CVD process. Furthermore, there are reports on the preparation of nano-silicon materials using silicate bacteria to extract silicon from minerals or tailings.

[0004] However, existing technologies still have the following shortcomings: First, existing silicon-carbon composite materials are mostly prepared using physical mixing or chemical deposition methods, resulting in weak interfacial bonding between functional layers. This makes them prone to interlayer delamination and structural failure during long-term cycling. Furthermore, the interfacial stability between silicon nanoparticles and the carbon matrix is ​​insufficient, making it difficult to effectively suppress silicon particle aggregation.

[0005] Second, the formation of hollow structures in existing technologies typically relies on template methods or chemical etching, which are complex and costly, and the size and porosity of the hollow structures are difficult to control precisely. The template removal process often involves strong acids, strong alkalis, or organic solvents, posing a risk of environmental pollution.

[0006] Third, the existing technical routes for preparing silicon-carbon materials using bacteria mostly involve first carbonizing bacterial cellulose to obtain a carbon skeleton, and then depositing a silicon layer through external means such as CVD. Essentially, these are still "two-step" or "three-step" physical / chemical deposition methods, which fail to fully utilize the integrated induction role of bacterial metabolic activity in silicon source dissociation, in-situ nanoparticle formation, and structural self-assembly.

[0007] Fourth, electrolytic manganese slag, a major industrial solid waste generated by the electrolytic manganese industry, contains abundant silicate mineral resources. However, its resource utilization rate is currently low, and its large-scale stockpiling causes serious environmental pressure. How to efficiently extract silicon from electrolytic manganese slag and convert it into high-value-added nano-silicon materials, while simultaneously achieving the resource utilization of solid waste, is an urgent technical challenge to be solved.

[0008] Fifth, the existing preparation process of silicon-carbon composite materials usually requires harsh conditions such as high-temperature (≥600℃) carbonization or chemical vapor deposition, which consumes a lot of energy and requires high-end equipment, making it unsuitable for large-scale production.

[0009] In view of this, the present invention is hereby proposed. Summary of the Invention

[0010] One of the objectives of this invention is to provide a bacterial-induced three-layer coated hollow silicon-based nanocomposite material to solve the technical problems of weak interlayer interface bonding, poor structural stability, complex hollow structure preparation process, single bacterial utilization method, high temperature and high energy consumption, and low solid waste resource utilization rate in existing silicon-carbon composite materials.

[0011] The second objective of this invention is to provide a method for preparing the above-mentioned three-layer coated hollow silicon-based nanocomposite material.

[0012] The third objective of this invention is to provide a silicon-carbon negative electrode sheet for lithium-ion batteries.

[0013] The fourth objective of this invention is to provide a lithium-ion battery.

[0014] In order to achieve the above-mentioned objectives of the present invention, the following technical solution is adopted: In a first aspect, the present invention provides a bacterial-induced three-layer coated hollow silicon-based nanocomposite material, wherein the composite material comprises, from the inside to the outside: The nano-silicon particle core is a nano-silicon stack formed by the self-assembly of silicon-containing mineral materials after biological weathering by mixed strains and in-situ dissociation and dissolution of silicon. The bacterial carbon isolation intermediate layer is a thin layer of biocarbon formed by in-situ degradation and carbonization of a mixed strain of Bacillus subtilis and Bacillus circulans. The bacterial carbon isolation intermediate layer continuously coats the outer side of the core of the nano-silicon particles. The organic carbon-coated outer layer is a porous carbon protective layer formed by solidifying an organic carbon source. The organic carbon-coated outer layer continuously and completely covers the outer surface of the bacterial carbon isolation intermediate layer.

[0015] Furthermore, the composite material includes at least one of the following features (1) to (6): (1) The particle size of the composite material is 20 nm to 2 μm, preferably 50 to 500 nm; (2) The particle size of the nano-silicon particles is uniformly distributed in the range of 5 to 20 nm, the crystallinity is 40% to 70%, and the porosity of the core is 15% to 45%. (3) The thickness of the bacterial carbon isolation intermediate layer is 5~30 nm; (4) The bacterial carbon isolation intermediate layer has a biological porous structure with a pore size of 2~10 nm; (5) The thickness of the organic carbon coating is 8~50 nm, and the specific surface area of ​​the carbon layer is 80~300 m². 2 / g, porosity 20%~50%; (6) The organic carbon coating outer layer and the bacterial carbon isolation intermediate layer also contain several hollow cavities, which are formed by the shrinkage of the bacterial cells.

[0016] Furthermore, the ratio of viable Bacillus subtilis to Bacillus circulans is 1:0.8 to 1:1.2, and the total viable count is ≥1.0 × 10⁻⁶. 9 CFU / mL.

[0017] Furthermore, the silicate mineral is an electrolytic manganese slag-based silicate powder; The electrolytic manganese slag-based silicate powder contains ≥60% muscovite and diopside by mass, and ≤20% framework quartz by mass.

[0018] The particle size of the electrolytic manganese slag-based silicate powder is 100~500 mesh; The organic carbon source is at least one of soluble sugars, polysaccharides, or sugar alcohols.

[0019] Furthermore, the organic carbon source is selected from at least one of glucose, sucrose, maltose, fructose, lactose, soluble starch, dextrin, or cellulose derivatives.

[0020] Furthermore, the silicon purity of the nano-silicon particle core is ≥85%, and the mass ratio of amorphous silicon to crystalline silicon is 3:7~6:4; The carbon-isolated intermediate layer of the bacteria contains ≥75% carbon and retains ≥60% of the original bioactive functional groups of the bacteria.

[0021] Secondly, the present invention provides a method for preparing the above-mentioned three-layer coated hollow silicon-based nanocomposite material, comprising the following steps: A. Raw material premixing and activation: The mixed bacterial solution of Bacillus mucilaginosus and Bacillus circularis is uniformly mixed with the silicate powder of electrolytic manganese slag, and activated by constant temperature shaking culture to obtain a bacterial-silicate composite premixed system with uniform activity. B. Surface organic carbon coating: Add an organic carbon source to the activated bacteria-silicate composite premix system and stir continuously until the system is homogeneous, so that the organic carbon source completely wets the surface of the powder particles and forms a uniform initial organic carbon coating film on the outer layer of the particles, thus obtaining the composite coating precursor. C. In-situ reaction nucleation and shell formation: The composite-coated precursor is placed at a constant temperature for static reaction. The mixed strains selectively dissolve silicate minerals through continuous metabolism, and silicon nanoparticles are generated in situ and accumulate in the core region inside the composite-coated precursor particles to form the nano-silicon particle core. At the same time, the bacteria gradually metabolize and degrade, and shrink in volume, forming an intermediate layer of bacterial residue on the outside of the nano-silicon particle core in situ. D. Low-temperature curing and shaping: The composite coating precursor after in-situ reaction is subjected to low-temperature curing and inert atmosphere carbonization treatment, so that the surface organic carbon source is solidified into a stable organic carbon coating outer layer, while the bacterial residue intermediate layer is carbonized and shaped to form a bacterial carbon isolation intermediate layer, thus obtaining a silicon-based nanocomposite material with a three-layer structure of nano-silicon particle core, bacterial carbon isolation intermediate layer, and organic carbon coating outer layer.

[0022] Furthermore, in step A, the solid-liquid ratio of the mixed bacterial solution to the electrolytic manganese slag silicate powder is 1 g:5 mL to 1 g:15 mL; The conditions for isothermal oscillation include 25~35℃ and 150~250 r / min; The activation culture time is 12~36 h; In step B, the solid-liquid mass ratio of the organic carbon source to the bacterial-silicate premixed system is 1:3 to 1:10.

[0023] Furthermore, in step C, the pH value of the isothermal static reaction system of the composite coating precursor is controlled to be 4.0–6.5; The isothermal static reaction time for the composite-coated precursor is 24~72 h; The temperature for the isothermal static reaction of the composite coating precursor is 25~35℃; In step D, the low-temperature curing process includes heating to 150-250°C at a heating rate of 2-5°C / min, with oxygen-free inert gas protection throughout the process, and heat preservation curing for 2-6 hours. The preparation method also includes a carbonization step, in which the temperature is raised to 600~900℃ at a heating rate of 2℃ / min, and oxygen-free inert gas is used for protection throughout the process, and the carbonization is carried out for 1~6 hours. During the carbonization process, the bacteria further shrink, forming a hollow cavity.

[0024] Thirdly, the present invention provides a silicon-carbon negative electrode sheet for a lithium-ion battery, wherein the active material of the negative electrode sheet comprises the above-mentioned three-layer coated hollow silicon-based nanocomposite material or the bacterial-induced three-layer coated hollow silicon-based nanocomposite material prepared by the above-mentioned preparation method.

[0025] Fourthly, the present invention provides a lithium-ion battery comprising the aforementioned silicon-carbon negative electrode, positive electrode, separator, and electrolyte.

[0026] The present invention provides a bacterial-induced three-layer coated hollow silicon-based nanocomposite material, which has the following beneficial effects: First, the functional division of the layers is clear: the nano-silicon particles are concentrated in the core, providing the maximum lithium storage active sites; the bacterial carbon, as the middle layer, uses its natural adhesion and encapsulation properties to closely adhere to the silicon core, exerting the best interface buffering effect; the outer organic carbon, as a sturdy shell, ensures the overall conductivity and structural integrity.

[0027] Second, the stress transmission path is optimized: during charging and discharging, the expansion force of the core silicon is transmitted from the inside to the outside. It is first buffered and reduced by the flexible bacterial carbon intermediate layer, and then transmitted to the outer hard carbon layer. Compared with the traditional structure in which the outer layer directly contacts the silicon, the "soft and hard combination" layer sequence design of this invention can more effectively suppress overall cracking.

[0028] Third, interfacial chemical stability: The functional groups retained in the bacterial carbon intermediate layer form strong hydrogen bonds or chemical bonds with the hydroxyl groups and other groups on the surface of the core nano-silicon, while being compatible with the oxygen-containing groups of the outer organic carbon, forming a continuous "silicon-biological carbon-organic carbon" bonding interface with high interfacial bonding strength. Attached Figure Description

[0029] To more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the drawings used in the description of the specific embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.

[0030] Figure 1 This is a schematic diagram of the structure of a bacterial-induced three-layer coated hollow silicon-based nanocomposite material provided in an embodiment of the present invention. Detailed Implementation

[0031] Unless otherwise defined herein, the scientific and technical terms used in conjunction with this invention shall have the meanings commonly understood by one of ordinary skill in the art. The meaning and scope of terms shall be clear; however, in any case of potential ambiguity, the definitions provided herein shall prevail over any dictionary or foreign definitions. In this application, unless otherwise stated, the use of "or" means "and / or". Furthermore, the use of the term "comprising" and other forms is non-limiting.

[0032] Unless otherwise stated, the methods and techniques of the present invention are generally carried out according to conventional methods well known in the art and as described in various general and more specific references, which are cited and discussed throughout this specification.

[0033] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0034] This invention provides a bacterial-induced three-layer coated hollow silicon-based nanocomposite material, wherein the composite material comprises, from the inside out: The nano-silicon particle core is a nano-silicon stack formed by the self-assembly of silicon-containing mineral materials after biological weathering by mixed strains and in-situ dissociation and dissolution of silicon. The bacterial carbon isolation intermediate layer is a thin layer of biocarbon formed by in-situ degradation and carbonization of a mixed strain of Bacillus subtilis and Bacillus circulans. The bacterial carbon isolation intermediate layer continuously coats the outer side of the core of the nano-silicon particles. The organic carbon-coated outer layer is a porous carbon protective layer formed by solidifying an organic carbon source. The organic carbon-coated outer layer continuously and completely covers the outer surface of the bacterial carbon isolation intermediate layer.

[0035] In this composite material, nano-silicon particles are concentrated in the core, providing maximized lithium storage active sites. Bacterial carbon, as an intermediate layer, utilizes its inherent adhesion and encapsulation properties to tightly adhere to the silicon core, achieving optimal interface buffering. The outer organic carbon layer serves as a robust outer shell, ensuring overall conductivity and structural integrity. During charging and discharging, the expansion force of the silicon core is transmitted from the inside out, first buffered and reduced by the flexible bacterial carbon intermediate layer, and then transmitted to the outer hard carbon layer. Compared to traditional structures where the outer layer directly contacts silicon, the "soft-hard combination" layered design of this invention can more effectively suppress overall cracking. The functional groups retained in the bacterial carbon intermediate layer form strong hydrogen bonds or chemical bonds with the hydroxyl groups and other groups on the surface of the nano-silicon core, while also being compatible with the oxygen-containing groups of the outer organic carbon layer, forming a continuous "silicon-biocarbon-organic carbon" bonding interface with high interfacial bonding strength.

[0036] In some specific embodiments, the particle size of the composite material is 20 nm to 2 μm, preferably 50 to 500 nm.

[0037] In some specific embodiments, the nano-silicon particle core has a uniform particle size distribution of 5-20 nm, a crystallinity of 40%-70%, and a core porosity of 15%-45%. In some specific embodiments, the silicon purity of the nano-silicon particle core is ≥85%, and the mass ratio of amorphous silicon to crystalline silicon is 3:7-6:4.

[0038] In some specific embodiments, the thickness of the bacterial carbon isolation interlayer is 5-30 nm; in some specific embodiments, the bacterial carbon isolation interlayer has a bioporous structure with a pore size of 2-10 nm. In some specific embodiments, the carbon content in the bacterial carbon isolation interlayer is ≥75%, and the retention rate of the original biologically active functional groups of the bacteria is ≥60%.

[0039] In some specific embodiments, the thickness of the organic carbon coating is 8-50 nm, and the specific surface area of ​​the carbon layer is 80-300 m². 2 / g, with a porosity of 20%~50%. In some specific embodiments, the organic carbon source is at least one of soluble sugars, polysaccharides, or sugar alcohols. In some specific embodiments, the organic carbon source is selected from at least one of glucose, sucrose, maltose, fructose, lactose, soluble starch, dextrin, or cellulose derivatives.

[0040] The composite material has an overall particle size of 50~500 nm, uniform distribution of silicon nanoparticles of 5~20 nm, and adjustable crystallinity of 40%~70%. Key parameters such as the thickness and porosity of the three-layer structure can be precisely adjusted by controlling process parameters such as strain ratio, reaction time, and carbon source dosage, and it has good structural designability.

[0041] In some specific embodiments, the organic carbon coating outer layer and the bacterial carbon isolation intermediate layer further include several hollow cavities, which are formed by the contraction of the bacterial cells.

[0042] In some specific embodiments, the silicate mineral is electrolytic manganese slag-based silicate powder; using electrolytic manganese slag as a silicon source, solid waste resource utilization is achieved. This invention directly uses electrolytic manganese slag-based silicate powder as raw material, and through bacterial bioweathering, dissolves and dissolves silicon in situ, transforming low-value industrial solid waste into high-value-added nano-silicon-based composite materials, while simultaneously solving the environmental problems associated with electrolytic manganese slag stockpiling. In some specific embodiments, the mass percentage of muscovite and diopside in the electrolytic manganese slag-based silicate powder is ≥60%, and the mass percentage of framework quartz is ≤20%; in some specific embodiments, the particle size of the electrolytic manganese slag-based silicate powder is 100~500 mesh.

[0043] According to another aspect of the present invention, a method for preparing the above-described three-layer coated hollow silicon-based nanocomposite material is also provided, comprising the following steps: A. Raw material premixing and activation: The mixed bacterial solution of Bacillus mucilaginosus and Bacillus circularis is uniformly mixed with the silicate powder of electrolytic manganese slag, and activated by constant temperature shaking culture to obtain a bacterial-silicate composite premixed system with uniform activity. B. Surface organic carbon coating: Add an organic carbon source to the activated bacteria-silicate composite premix system and stir continuously until the system is homogeneous, so that the organic carbon source completely wets the surface of the powder particles and forms a uniform initial organic carbon coating film on the outer layer of the particles, thus obtaining the composite coating precursor. C. In-situ reaction nucleation and shell formation: The composite-coated precursor is placed at a constant temperature for static reaction. The mixed strains selectively dissolve silicate minerals through continuous metabolism, and silicon nanoparticles are generated in situ and accumulate in the core region inside the composite-coated precursor particles to form the nano-silicon particle core. At the same time, the bacteria gradually metabolize and degrade, and shrink in volume, forming an intermediate layer of bacterial residue on the outside of the nano-silicon particle core in situ. D. Low-temperature curing and shaping: The composite coating precursor after in-situ reaction is subjected to low-temperature curing and inert atmosphere carbonization treatment, so that the surface organic carbon source is solidified into a stable organic carbon coating outer layer, while the bacterial residue intermediate layer is carbonized and shaped to form a bacterial carbon isolation intermediate layer, thus obtaining a silicon-based nanocomposite material with a three-layer structure of nano-silicon particle core, bacterial carbon isolation intermediate layer, and organic carbon coating outer layer.

[0044] Through the synergistic metabolic action of Bacillus subtilis and Bacillus circulatoryus, bacterial-induced in-situ layer-by-layer molding is achieved on an electrolytic manganese slag silicate powder substrate. The layer structure exhibits high interfacial bonding strength and no delamination, effectively inhibiting the aggregation and volume expansion of silicon nanoparticles. The bacterial metabolic activity enables the in-situ dissociation of silicon elements in silicate minerals and the self-assembly of silicon nanoparticles, avoiding the need for external chemical reagents and high-temperature treatment. The overall molding of the composite material is completed under mild conditions, reducing energy consumption and production costs.

[0045] In some specific embodiments, in step A, the solid-liquid ratio of the mixed bacterial solution to the electrolytic manganese slag silicate powder is 1 g:5 mL to 1 g:15 mL. In some specific embodiments, the ratio of viable Bacillus subtilis to Bacillus circulans in the mixed bacterial solution is 1:0.8 to 1:1.2, and the total viable count is ≥1.0 × 10⁻⁶. 9 CFU / mL.

[0046] In some specific implementations, the isothermal oscillation conditions include 25~35℃ and 150~250 r / min; in some specific implementations, the activation culture time is 12~36 h.

[0047] In some specific implementations, in step B, the solid-liquid mass ratio of the organic carbon source to the bacterial-silicate premixed system is 1:3 to 1:10.

[0048] In some specific embodiments, in step C, the pH value of the isothermal static reaction system of the composite coating precursor is controlled to be 4.0 to 6.5; in some specific embodiments, the isothermal static reaction time of the composite coating precursor is 24 to 72 h; in some specific embodiments, the isothermal static reaction temperature of the composite coating precursor is 25 to 35°C.

[0049] In some specific implementations, in step D, the low-temperature curing process includes heating to 150-250°C at a heating rate of 2-5°C / min, using oxygen-free inert gas protection throughout the process, and maintaining the temperature for 2-6 hours.

[0050] In some specific embodiments, the preparation method further includes a carbonization step, in which the temperature is raised to 600~900℃ at a heating rate of 2℃ / min, and the entire process is protected by an oxygen-free inert gas, and the carbonization is carried out for 1~6 hours.

[0051] In some specific embodiments, during the carbonization process, the microbial cells further shrink to form hollow cavities.

[0052] According to another aspect of the present invention, a silicon-carbon negative electrode sheet for a lithium-ion battery is also provided, wherein the active material of the negative electrode sheet comprises the above-mentioned three-layer coated hollow silicon-based nanocomposite material or the bacterial-induced three-layer coated hollow silicon-based nanocomposite material prepared by the above-mentioned preparation method.

[0053] According to another aspect of the present invention, a lithium-ion battery is also provided, comprising the above-described silicon-carbon negative electrode, positive electrode, separator, and electrolyte.

[0054] The present invention will be further illustrated below by way of examples. Unless otherwise specified, the materials in the examples are prepared according to existing methods or purchased directly from the market.

[0055] Paenibacillus mucilaginosus is deposited at the China General Microbiological Culture Collection Center, with strain number CGMCC 1.2326.

[0056] Bacillus circulans is deposited at the China Industrial Microbial Culture Collection Center, with strain number CICC 20762.

[0057] Example 1 A bacterial-induced shaped three-layer coated hollow silicon-based nanocomposite material is prepared according to the following steps: Step 1: Raw material premixing and activation A mixed bacterial suspension was prepared by mixing Paenibacillus mucilaginosus and Bacillus circulans at a viable count ratio of 1:1, with a total viable count of 1.5 × 10⁻⁶. 9 CFU / mL. Electrolytic manganese slag-based silicate powder (particle size 200 mesh, total mass percentage of muscovite and diopside layered silicate minerals 65%, mass percentage of quartz 15%) was mixed with the above mixed bacterial solution at a solid-liquid ratio of 1 g: 10 mL and placed in a constant temperature shaking incubator. The mixture was shaken and activated for 24 h at 30℃ and 200 r / min to obtain a uniformly active bacteria-silicate composite premixed system.

[0058] Step 2: Surface organic carbon coating Soluble starch (the solid-liquid mass ratio of soluble starch to bacterial-silicate premix is ​​1:5) is added to the activated bacterial-silicate composite premix system, and the mixture is continuously stirred (stirring speed 400 rpm, time 60 min) until the system is homogeneous, so that the organic carbon source completely wets the surface of the powder particles and forms a uniform initial organic carbon coating film on the outer layer of the particles, thus obtaining the composite coating precursor.

[0059] Step 3: In-situ reaction for nucleation and shell formation The composite-coated precursor was incubated at 30 °C for 48 h. During the reaction, the mixed bacterial strain continuously metabolized and produced acids, secreting organic acids and biochelating agents. These selectively dissolved the layered silicate mineral lattice in the electrolytic manganese slag, releasing silicate ions which then nucleated and grew into silicon nanoparticles on and around the bacterial surface. These nanoparticles self-assembled to form silicon nanoparticles (approximately 45 nm thick, with a particle size of 8–15 nm and a crystallinity of approximately 55%). Simultaneously, the bacterial cells gradually metabolized and degraded, shrinking in volume. An intermediate layer of bacterial residue was formed in situ outside the silicon core, spontaneously forming hollow cavities (cavity spacing 20–100 nm) with the outermost organic carbon coating layer inside the particles. The pH of the reaction system was stably maintained at 4.5–5.5 under the autonomous metabolic regulation of the bacterial strain.

[0060] Step 4: Low-temperature curing and setting The composite system after the in-situ reaction was subjected to low-temperature curing treatment. Under nitrogen protection, the temperature was increased to 200 °C at a rate of 3 °C / min and held for curing for 4 h. This allowed the surface organic carbon source to solidify into a stable organic carbon-coated outer layer (approximately 25 nm thick, with a specific surface area of ​​approximately 180 m² / g and a porosity of approximately 35%). Simultaneously, the intermediate layer of bacterial residue was carbonized and shaped, forming a bacterial carbon-isolated intermediate layer (approximately 15 nm thick, with pore sizes of 4–8 nm). After curing, the mixture was naturally cooled to room temperature to obtain the precursor of the three-layer coated hollow silicon-based nanocomposite material, with the structure shown below. Figure 1 As shown.

[0061] Step 5: Carbonization The precursor complex was placed in a tube furnace and heated to 650°C at a rate of 2°C / min under a nitrogen atmosphere (flow rate 100 mL / min). The temperature was maintained for 2 hours, followed by the introduction of a hydrogen-argon mixture (flow rate 150 mL / min) and continued to maintain the temperature for 1 hour, then allowed to cool naturally.

[0062] The purpose of introducing the hydrogen-argon mixture is to reduce silicon oxide into nano-silicon particles.

[0063] Example 2 The difference from Example 1 is as follows: In step 1: the ratio of viable bacteria of the mixed strain *Bacillus mucilaginosus* to *Bacillus circulans* was 1:0.8, and the total viable bacteria count of the mixed bacterial solution was 1.0 × 10⁻⁶. 9 CFU / mL; electrolytic manganese slag silicate powder particle size is 100 mesh; solid-liquid ratio is 1 g:5 mL; activation temperature is 25 ℃, activation time is 36 h, and oscillation speed is 150 r / min.

[0064] In step 2: the organic carbon source is glucose, and the solid-liquid mass ratio of the organic carbon source to the bacterial-silicate premixed system is 1:3.

[0065] In step 3: the in-situ reaction temperature is 25 ℃ and the reaction time is 72 h.

[0066] In step 4: the curing temperature is 150 ℃, the curing time is 6 h, and the heating rate is 2 ℃ / min.

[0067] Example 3 The difference from Example 1 is as follows: In step 1: the ratio of viable bacteria of the mixed strain *Bacillus mucilaginosus* to *Bacillus circulans* was 1:1.2, and the total viable bacteria count of the mixed bacterial solution was 2.0 × 10⁻⁶. 9 CFU / mL; electrolytic manganese slag silicate powder particle size of 500 mesh; solid-liquid ratio of 1 g:15 mL; activation temperature of 35 ℃, activation time of 12 h, and oscillation speed of 250 r / min.

[0068] In step 2: the organic carbon source is an equal mass mixture of sucrose and soluble starch, and the solid-liquid mass ratio of the organic carbon source to the bacterial-silicate premix system is 1:10.

[0069] In step 3: the in-situ reaction temperature is 35 ℃ and the reaction time is 24 h.

[0070] In step 4: the curing temperature is 250 ℃, the curing time is 2 h, and the heating rate is 5 ℃ / min.

[0071] Example 4 The difference from Example 1 is as follows: In step 2: the organic carbon source is sucrose, and the solid-liquid mass ratio of the organic carbon source to the bacterial-silicate premixed system is 1:7.

[0072] In step 3: the pH value of the in-situ reaction is stably maintained at 5.5-6.5.

[0073] In step 4: the curing temperature is 220 ℃ and the curing time is 3 h.

[0074] Example 5 The difference from Example 1 is as follows: In step 1: the ratio of viable bacteria of the mixed strain *Bacillus mucilaginosus* to *Bacillus circulans* was 1:1.1, and the total viable bacteria count of the mixed bacterial solution was 1.8 × 10⁻⁶. 9 CFU / mL; electrolytic manganese slag silicate powder particle size is 300 mesh; solid-liquid ratio is 1 g:12 mL; activation temperature is 32 ℃, activation time is 18 h, and oscillation speed is 220 r / min.

[0075] In step 2: the organic carbon source is an equal mass mixture of glucose and soluble starch, and the solid-liquid mass ratio of the organic carbon source to the bacterial-silicate premix system is 1:6.

[0076] In step 3: the in-situ reaction temperature was 32 ℃, and the reaction time was 40 h. The pH value of the reaction system was stably maintained at 4.8–5.8 under the autonomous metabolic regulation of the strain.

[0077] In step 4: the curing temperature is 180 ℃, the curing time is 5 h, and the heating rate is 4 ℃ / min.

[0078] Table 1. Basic physical properties of the three-layer coated hollow silicon-based nanocomposites prepared in Examples 1-5

[0079] Comparative Example 1 The difference from Example 1 is that no organic carbon source is added for surface coating, that is, step S2 is omitted, and the in-situ reaction of step S3 and the curing treatment of step S4 are carried out directly on the bacterial-silicate composite premix system.

[0080] Comparative Example 2 The difference between this comparative example and Example 1 is that only a single strain of Bacillus mucilaginosa is used in step S1, and Bacillus circulans is not used.

[0081] Comparative Example 3 The difference between this comparative example and Example 1 is that the in-situ reaction time in step S3 is 12 h (less than 24 h).

[0082] The silicon-carbon composite materials obtained in each embodiment and comparative example were tested using the following testing methods: 1. Test of Si content in silicon-carbon composite materials: 3.0 g of silicon-carbon composite material was dried in a 150℃ oven until constant weight, and the mass m1 was recorded. The dried composite material was then placed in a muffle furnace, heated to 1100℃ and held for 2 hours, cooled, and weighed, and the mass m2 was recorded. The Si content calculation formula is as follows: .

[0083] 2. Specific surface area: Tested using a Bestar specific surface area tester (BSD-PS type).

[0084] 3. Half-cell test method: The electrochemical performance of the silicon-carbon composite materials obtained in Examples 1-5 and Comparative Examples 1-3 was tested, and the results are shown in Table 2. Using the silicon-carbon composite materials obtained in Examples 1-5 and Comparative Examples 1-3 as the negative electrode active material, negative electrode sheets were prepared. CR2032 coin cells were fabricated using conventional methods, and the electrical performance of the cells was tested. Charge-discharge tests were performed on the cells using the LAND battery testing system.

[0085] (1) Half-cell assembly: Assemble CR2032 button cells in a glove box, with lithium metal sheet as counter electrode, polypropylene microporous membrane as separator, and LiPF6 dissolved in a mixture of ethyl carbonate (EC) and diethyl carbonate (DEC) (volume ratio EC:DEC=1:1), wherein the concentration of LiPF6 is 1mol / L.

[0086] (2) Cyclic specific capacity and initial efficiency test: After the CR2032 button cell was left to stand for 6 hours, it was discharged to 0.005V at 0.05C and then discharged to 0.005V at 0.01C; after standing for 5 minutes, it was charged to 1.5V at a constant current of 0.05C; the initial delithiation specific capacity at 0.8V is the specific capacity (or mass specific capacity) of the electrode material at 0.8V, and the ratio of the initial delithiation specific capacity at 0.8V to the initial lithium insertion specific capacity at 1.5V is the initial coulombic efficiency at 0.8V of the battery.

[0087] (3) 25℃, 2C / 0.2C rate retention test: After the CR2032 coin cell was left to stand for 6 hours, it was discharged at 0.2C to 0.005V, left to stand for 5 minutes, and then charged at 0.2C to 1.5V. This cycle was repeated 3 times. Subsequently, it was discharged at 2C to 0.005V, left to stand for 5 minutes, and then charged at 2C to 1.5V. This cycle was repeated 3 times. The data were recorded, and the 2C lithium intercalation retention rate was the 2C discharge specific capacity / 0.2C discharge specific capacity. The results are shown in Table 2.

[0088] 4. Full battery testing method: Using the silicon-carbon composite materials obtained in Examples 1-5 and Comparative Examples 1-3 as the negative electrode active material, pouch cells containing the negative electrode active material were prepared using conventional methods, and their electrical performance was tested. The pouch cells were prepared in a dehumidified room at a dew point of -45°C. Charge-discharge cycle tests were performed on the cells using the LANBTS battery testing system. The specific test method is as follows: (1) Preparation of positive electrode sheet: The positive electrode active material LiCoO2, conductive agent Super P, binder PVDF and solvent NMP are mixed evenly in a mass ratio of 92:3:5:150 and then evenly coated on the positive electrode current collector. Then, it is dried at 80℃ to obtain the positive electrode sheet.

[0089] (2) Preparation of negative electrode sheet: The negative electrode active material, conductive agent SP, binder PAA, thickener CMC, binder SBR and solvent deionized water are mixed evenly in a mass ratio of 95:1:2:1:1:120 and then evenly coated on the negative electrode current collector. After drying at 80°C, the negative electrode sheet is obtained by roller pressing.

[0090] (3) The positive and negative electrode sheets are stacked in a square and separated by a polypropylene separator to form a battery cell, which is then packaged into an aluminum-plastic bag. An electrolyte of the appropriate capacity is injected into the aluminum-plastic bag, and the bag is vacuum sealed to obtain a soft-pack battery. The electrolyte is a mixture of LiPF6 EC and DEC, wherein the concentration of LiPF6 is 1 mol / L and the volume ratio of EC to DEC is 1:1.

[0091] (4) Formation and Capacity Testing: After liquid injection and sealing, the battery begins formation. It is placed in a constant temperature chamber at 25°C for 12 hours, then charged at a constant current of 0.02C to 3.3V, placed for 30 minutes, charged at a constant current of 0.025C to 3.8V, placed for 10 minutes, and charged at a constant current of 0.33C to 4.2V. After formation, the battery is vacuum-sealed and then subjected to capacity testing. It is charged at a constant current of 0.33C to 4.45V, placed for 10 minutes, discharged at a constant current of 1C to 3V, placed for 10 minutes, and discharged at a constant current of 0.33C to 3V. The capacity testing is then completed. The ratio of the discharge capacity to the charge capacity during the formation and capacity testing of the pouch battery is the initial efficiency of the battery.

[0092] (5) 25℃, 1C cycle test: Place the battery in a 25℃ constant temperature chamber and charge it to 4.45V with a constant current of 1C, and then charge it to 0.1C with a constant voltage of 4.45V. After standing for 10 minutes, discharge it to 3.0V with a constant current of 1C and stand for 10 minutes. Repeat the above charging and discharging steps until the discharge capacity is lower than 80% of the discharge capacity of the first cycle. The number of cycles obtained at this time is the cycle life of the soft pack battery. Record the capacity retention rate after 100 cycles. The results are shown in Table 2.

[0093] Table 2. Electrochemical performance and response data of silicon-carbon composite materials prepared in Examples 1-5 and Comparative Examples 1-3.

[0094] As shown in Table 1, Example 1 exhibits the best overall electrochemical performance among the five examples: silicon content 42.5 wt%, 0.8V specific capacity 1680 mAh / g, 0.8V initial efficiency 86.5%, 2C / 0.2C rate retention 68.2%, and 1C / 100 cycles capacity retention 98.5%. All five core indicators are at a leading level, indicating that its process parameter combination (1:1 strain ratio, soluble starch carbon source, 48 h in-situ reaction, and 200 °C curing) achieved the best synergistic effect. Example 5 is the second best, verifying the good reproducibility of the invention under similar process conditions. Although Example 3 has the highest silicon content (45.0 wt%), the higher silicon content leads to a slight decrease in the capacity contribution per unit of silicon, and its rate performance is slightly inferior to Example 1, indicating that higher silicon content is not always better; there is an optimal value range. Example 2, due to its lower curing temperature (150 ℃), has a slightly lower degree of graphitization of the carbon layer and slightly weaker conductivity. Therefore, all performance indicators are the lowest among the five examples, but are still far superior to the comparative examples, indicating that the optimal process window of the present invention has a certain degree of redundancy.

[0095] Compared to Example 1 (without outer coating), Comparative Example 1 (without outer coating) showed a capacity loss of 300 mAh / g (-17.9%) at 0.8V and a 1C / 100 cycle retention rate that plummeted from 90.5% to 75.0% (a decrease of 15.5 percentage points), indicating that the organic carbon coating plays a decisive role in maintaining long-term cycling stability.

[0096] Comparative Example 2 (single strain) compared to Example 1: silicon content was only 35.0 wt% (lower than 42.5 wt% in Example 1), 0.8V specific capacity loss was 430 mAh / g (-25.6%), and the 2C / 0.2C rate retention decreased from 68.2% to 58.2% (a decrease of 10 percentage points). This indicates that the silicon dissolution efficiency of the single strain is insufficient, resulting in significantly lower silicon content and silicon crystallinity compared to the dual-strain synergistic system.

[0097] Comparative Example 3 (insufficient reaction time) compared to Example 1: The silicon content was only 32.0 wt%, the 0.8V specific capacity loss was 530 mAh / g (-31.5%), and the 1C / 100 cycle retention rate was only 65.0%, less than 72% of Example 1. This indicates that insufficient reaction time led to incomplete dissolution of silicate minerals, incomplete development of hollow cavities, and incomplete formation of the three-layer structure, fundamentally deteriorating the various electrochemical properties of the composite material. In the embodiments of this invention, the silicon content ranged from 38.0 to 45.0 wt%, and the 0.8V specific capacity ranged from 1550 to 1680 mAh / g, showing a good linear positive correlation (R0). 2=0.89), with an average capacity contribution of 38.7 mAh / g·wt% per unit silicon content, indicating that silicon in the composite material of this invention is efficiently utilized. The silicon nanoparticles are uniformly distributed in the intermediate layer in a highly active crystalline form without significant electrochemical inert aggregation. Meanwhile, although the silicon content of Comparative Example 2 (single strain) and Comparative Example 3 (insufficient reaction) is low, their capacity contribution per unit silicon is also significantly low (35.7 mAh / g·wt% and 35.9 mAh / g·wt%, respectively), indicating that the inferior microstructure reduces both silicon loading and utilization, and the combination of the two leads to severe capacity degradation.

[0098] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A bacterial-induced, three-layer-coated hollow silicon-based nanocomposite material, characterized in that, The composite material comprises, from the inside out: The nano-silicon particle core is a nano-silicon stack formed by the self-assembly of silicon-containing mineral materials after biological weathering by mixed strains and in-situ dissociation and dissolution of silicon. The bacterial carbon isolation intermediate layer is a thin layer of biocarbon formed by in-situ degradation and carbonization of a mixed strain of Bacillus subtilis and Bacillus circulans. The bacterial carbon isolation intermediate layer continuously coats the outer side of the core of the nano-silicon particles. The organic carbon-coated outer layer is a porous carbon protective layer formed by solidifying an organic carbon source. The organic carbon-coated outer layer continuously and completely covers the outer surface of the bacterial carbon isolation intermediate layer.

2. The composite material according to claim 1, characterized in that, The composite material includes at least one of the following features (1) to (6): (1) The particle size of the composite material is 20 nm to 2 μm; (2) The particle size of the nano-silicon particles is uniformly distributed in the range of 5 to 20 nm, the crystallinity is 40% to 70%, and the porosity of the core is 15% to 45%. (3) The thickness of the bacterial carbon isolation intermediate layer is 5~30 nm; (4) The bacterial carbon isolation intermediate layer has a biological porous structure with a pore size of 2~10 nm; (5) The thickness of the organic carbon coating is 8~50 nm, and the specific surface area of ​​the carbon layer is 80~300 m². 2 / g, porosity 20%~50%; (6) The organic carbon coating outer layer and the bacterial carbon isolation intermediate layer also contain several hollow cavities, which are formed by the shrinkage of the bacterial cells.

3. The composite material according to claim 1, characterized in that, The ratio of viable Bacillus subtilis to viable Bacillus circulans is 1:0.8 to 1:1.2, and the total viable count is ≥1.0 × 10⁻⁶. 9 CFU / mL.

4. The composite material according to claim 1, characterized in that, The silicate mineral is an electrolytic manganese slag-based silicate powder; The electrolytic manganese slag-based silicate powder contains ≥60% muscovite and diopside by mass, and ≤20% framework quartz by mass. The particle size of the electrolytic manganese slag-based silicate powder is 100~500 mesh; The organic carbon source is at least one of soluble sugars, polysaccharides, or sugar alcohols.

5. The composite material according to claim 1, characterized in that, The silicon purity of the nano-silicon particle core is ≥85%, and the mass ratio of amorphous silicon to crystalline silicon is 3:7~6:

4. The carbon-isolated intermediate layer of the bacteria contains ≥75% carbon and retains ≥60% of the original bioactive functional groups of the bacteria.

6. The method for preparing the three-layer coated hollow silicon-based nanocomposite material according to any one of claims 1 to 5, characterized in that, Includes the following steps: A. Raw material premixing and activation: The mixed bacterial solution of Bacillus mucilaginosus and Bacillus circularis is uniformly mixed with the silicate powder of electrolytic manganese slag, and activated by constant temperature shaking culture to obtain a bacterial-silicate composite premixed system with uniform activity. B. Surface organic carbon coating: Add an organic carbon source to the activated bacteria-silicate composite premix system and stir continuously until the system is homogeneous, so that the organic carbon source completely wets the surface of the powder particles and forms a uniform initial organic carbon coating film on the outer layer of the particles, thus obtaining the composite coating precursor. C. In-situ reaction nucleation and shell formation: The composite-coated precursor is placed at a constant temperature for static reaction. The mixed strains selectively dissolve silicate minerals through continuous metabolism, and silicon nanoparticles are generated in situ and accumulate in the core region inside the composite-coated precursor particles to form the nano-silicon particle core. At the same time, the bacteria gradually metabolize and degrade, and shrink in volume, forming an intermediate layer of bacterial residue on the outside of the nano-silicon particle core in situ. D. Low-temperature curing and shaping: The composite coating precursor after in-situ reaction is subjected to low-temperature curing and inert atmosphere carbonization treatment, so that the surface organic carbon source is solidified into a stable organic carbon coating outer layer, while the bacterial residue intermediate layer is carbonized and shaped to form a bacterial carbon isolation intermediate layer, thus obtaining a silicon-based nanocomposite material with a three-layer structure of nano-silicon particle core, bacterial carbon isolation intermediate layer, and organic carbon coating outer layer.

7. The preparation method according to claim 6, characterized in that, In step A, the solid-liquid ratio of the mixed bacterial solution to the electrolytic manganese slag silicate powder is 1 g:5 mL to 1 g:15 mL; The conditions for isothermal oscillation include 25~35℃ and 150~250 r / min; The activation culture time is 12-36 h; In step B, the solid-liquid mass ratio of the organic carbon source to the bacterial-silicate premixed system is 1:3 to 1:

10.

8. The preparation method according to claim 6, characterized in that, In step C, the pH value of the isothermal static reaction system of the composite coating precursor is controlled to be 4.0–6.5; The isothermal static reaction time for the composite-coated precursor is 24~72 h; The temperature for the isothermal static reaction of the composite coating precursor is 25~35℃; In step D, the low-temperature curing process includes heating to 150-250°C at a heating rate of 2-5°C / min, with oxygen-free inert gas protection throughout the process, and heat preservation curing for 2-6 hours. The preparation method also includes a carbonization step, in which the temperature is raised to 600~900℃ at a heating rate of 2℃ / min, and oxygen-free inert gas is used for protection throughout the process, and the carbonization is carried out for 1~6 hours. During the carbonization process, the bacteria further shrink, forming a hollow cavity.

9. A silicon-carbon negative electrode sheet for a lithium-ion battery, characterized in that, The active material of the negative electrode sheet comprises the three-layer coated hollow silicon-based nanocomposite material as described in any one of claims 1 to 5, or the bacterial-induced three-layer coated hollow silicon-based nanocomposite material prepared by the preparation method described in any one of claims 6 to 8.

10. A lithium-ion battery, characterized in that, It includes the silicon-carbon negative electrode, positive electrode, separator, and electrolyte as described in claim 9.